Gambaran sementoblastoma tahap awal pada cone beam computed tomography (CBCT) 3D - Rellyca Sola Gracea; Ria Noerianingsih Firman (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The purpose of this study was to report a case of mandibular cementoblastoma with radiologic approach and describe its characteristics. Case Report: A 32-year-old female came to the Hospital and complained of swelling of the left side of the lower jaw. Clinical examination showed a strong swelling in the buccal region of teeth 44-45, with the same soft tissue color as the surrounding tissue. In the picture cone beam computed tomography appears as a rounded lesion, the internal structure of the radiointermediet with clear and firm boundaries, surrounded by a halo radiolucent. Cementoblastoma radiodiagnosis is established. The patient was referred for surgery. Conclusion: Cementoblastoma was a benign tumor with radiographic characteristics in the form of clearly demarcated radiopaque lesion with radiolucent halo. Some early-stage lesions can show lower density.